A review of the powderpost beetle genera Xylothrips Lesne, 1901 and Calophagus Lesne, 1902 (Coleoptera: Bostrichidae: Bostrichinae: Xyloperthini) - Liu, Lan-Yu (European Journal of Taxonomy, 2021)
This paper reviews the genera Xylothrips Lesne, 1901 and Calophagus Lesne, 1902, and their species, and proposes that Calophagus should be reinstated as a full genus from a subgenus of Xylothrips (contra Borowski & Węgrzynowicz 2019). The genera and their included species are diagnosed and redescribed, and a summary of information on the distribution and biology of all species is provided. The importance of characters of the antennal club and pronotum in separating the two genera is stressed. A key to the two genera and the two species of Xylothrips is provided.